Biological versus Clinical Risk Factors in Acute Myeloid Leukemia: Is There a Winner? - M. Malagola; N. Polverelli; V. Cancelli; E. Morello; A. Turra; E. Borlenghi; F. Cattina; B. Rambaldi; S. Bernardi; C. Zanaglio; Elif Dereli Eke; L. Gandolfi; et al. (Case Reports in Hematology)
We present a case of a patient with a three-month history of peripheral blood cytopenia without a confirmed diagnosis of myelodysplastic syndrome, who developed a favourable-risk acute myeloid leukemia (AML), according to the European Leukemia Net (ELN) criteria. The patient achieved a complete remission with incomplete platelet recovery (CRi) after induction. The patient achieved the morphological CR after the first consolidation and completed the first-line treatment with a syngeneic stem cell transplantation (SCT). A disease relapse occurred after one year of CR (blast cell count in the bone marrow 15%), and the patient was offered a haplo-SCT, which he refused due to personal reasons. In this paper, we discuss the interplay between clinical and biological risk factors in non-high-risk AML patients and speculate that some old clinical risk factors (e.g., age of the patient, achievement of CR after induction, and previous history of myelodysplastic syndrome) may still impact on the treatment decision algorithm of some of these patients.